No association of TNFRSF1B variants with type 2 diabetes in Indians of Indo-European origin - Ghosh Saurabh; Kundu Bratashree; Sharma Vasudha; Dubey Himanshu; Dwivedi Om; Chauhan Ganesh; Mahajan Anubha; Tabassum Rubina; Tandon Nikhil; Bharadwaj Dwaipayan (BMC, 2011)
Abstract Background There has been no systematic evaluation of the association between genetic variants of type 2 receptor for TNFα (TNFR2) and type 2 diabetes, despite strong biological evidence for the role of this receptor in the pathogenesis of this complex disorder. In view of this, we performed a comprehensive association analysis of TNFRSF1B variants with type 2 diabetes in 4,200 Indo-European subjects from North India. Methods The initial phase evaluated association of seven SNPs viz. rs652625, rs496888, rs6697733, rs945439, rs235249, rs17883432 and rs17884213 with type 2 diabetes in 2,115 participants (1,073 type 2 diabetes patients and 1,042 control subjects). Further, we conducted replication analysis of three associated SNPs in 2,085 subjects (1,047 type 2 diabetes patients and 1,038 control subjects). Results We observed nominal association of rs945439, rs235249 and rs17884213 with type 2 diabetes (P < 0.05) in the initial phase. Haplotype CC of rs945439 and rs235249 conferred increased susceptibility for type 2 diabetes [OR = 1.19 (95%CI 1.03-1.37), P = 0.019/Pperm = 0.076] whereas, TG haplotype of rs235249 and rs17884213 provided protection against type 2 diabetes [OR = 0.83 (95%CI 0.72-0.95, P = 7.2 × 10-3/Pperm = 0.019]. We also observed suggestive association of rs496888 with plasma hsCRP levels [P = 0.042]. However, the association of rs945439, rs235249 and rs17884213 with type 2 diabetes was not replicated in the second study population. Meta-analysis of the two studies also failed to detect any association with type 2 diabetes. Conclusions Our two-stage association analysis suggests that TNFRSF1B variants are not the determinants of genetic risk of type 2 diabetes in North Indians.